External oblique intercostal block in open nephrectomy patients - A zenith in analgesia for anterolateral upper abdominal surgeries: A case series - Priyanka Bansal; Nidhi Sultania; Tarun Mittal (Asian Journal of Medical Sciences, 2024)
Open nephrectomy is a common surgery usually performed for malignant and non-malignant renal pathologies. The external oblique intercostal block (EOIB) blocks the anterior and lateral cutaneous nerves from T6 to T10 and provides somatic analgesia. We present a case series of the use of EOIB in patients undergoing open nephrectomy by subcostal incision. Ten patients were given EOIB, which included patients undergoing simple nephrectomy for non-functioning kidneys and radical nephrectomy for renal mass. The patients had satisfactory numerical rating scale scores, mostly <4 for 24 h. Post-operative opioid consumption was minimal. The external oblique fascial plain block is a novel thoracic block that provides reliable upper thoracoabdominal somatic analgesia. It can certainly be considered a suitable option in surgeries such as nephrectomies that involve an upper lateral abdominal wall incision.